Hubungan Kepatuhan Perawat dengan Perilaku Pencegahan Ventilator Associated Pneumonia (Vap) Di Ruang Icu,Picu RSUD Undata Provinsi Sulawesi Tengah: Penelitian - Alita Jawayanti; Abdul Rahman; Benny H.L Situmorang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Background: Ventilator-Associated Pneumonia (VAP) is a common nosocomial infection in the Intensive Care Unit (ICU) and Pediatric Intensive Care Unit (PICU) that significantly increases mortality, length of hospital stay, and healthcare costs. Nurses’ compliance with the VAP bundle plays a crucial role in preventing VAP. Objective: To analyze the relationship between nurses’ compliance levels and VAP prevention behaviors in the ICU and PICU of Undata Regional Hospital. Methods: This quantitative study used a cross-sectional design involving 32 nurses selected through total sampling. Data were collected using a compliance questionnaire and an observation checklist, then analyzed using Fisher’s Exact Test. Results: Most nurses demonstrated high compliance (62.5%) and good VAP prevention behaviors (81.3%). Bivariate analysis showed a significant relationship (p = 0.001).Conclusion: There is a significant association between nurses’ compliance and VAP prevention behaviors. Recommendation: Hospitals should strengthen regular monitoring, compliance audits, and continuous training to reduce VAP incidence.